Effect of ultraviolet irradiation with dean vortex technology on quality of pineapple-mango juice blend - Kamarul Zaman, Amanina Amani (2018)
Conventional thermal pasteurisation is more preferable by juice processor in microorganism inactivation due to its effectiveness but results in nutritional and quality degradation. Due to that, the alternative non-thermal technology of ultravioletirradiation (UV-C) gaining interest to minimise the stated effects. Application of UV-C in single fruit juice already well explored compared to a juice blend. Thus, this present research aimed to investigate the effect of UV-C on the quality attributes of pineapplemango juice blend. Pineapple-mango juice blend at blending ratio of (pineapple to mango) 70:30 (v/v), exhibit best results of ascorbic acid, total phenolic with lowest turbidity value compared to blending ratios of 50:50 and 30:70. Colour appearance of pineapple-mango juice blend at all different blending ratios was not significantly different. Pineapple-mango juice blend at blending ratio of 70:30 were selected for further preservation treatment. UV-C dosage of 8.38mJ/cm² able to reduce the microbial load (Escherichia coli O157: H7, total plate count, yeast and mould count) to safety limit of 5-log reduction. Storage of 9 weeks at 4°C of pineapple-mango juice blends resulted in significant changes in pH, total soluble solids, turbidity and DPPH assay (p<0.05) of untreated, thermal and UV-C treated juice. Although, the ascorbic acid and total phenolic content of UV-C treated pineapple-mango juice blend was decreasing (p<0.05) the values were higher compared to thermally treated juice. Colour degradation (lightness, hue, chroma, browning index, colour difference (ΔE) and nonenzymatic browning) of thermally treated pineapple-mango juice blend was also prominent in thermally treated juice compared to UV-C treated juice. During storage, reoccurrence of microbiological activities of UV-C and thermally treated pineapplemango juice blend observed starting at week 3 and 5 respectively. Kinetic model of ΔE during storage of the untreated and thermally pineapple-mango juice blend fitted to zero order model, while UV-C treated fitted to first order. Ascorbic acid degradation of untreated, UV-C and thermally treated pineapple-mango juice blend best fitted to modified first order model indicate storage time together with other parameter such as pH, temperature and oxygen contribute to the degradation rate. The present study showing promising effect of UV-C treatment in preserving the quality of pineapplemango juice blend.